A comprehensive study of the academic benefits and practical recommendations to include resistance training programs in institutional education - Fraile-Martinez, Oscar; García-Montero, Cielo; Fraile-Martinez, Marcos; Pekarek, Leonel; Barrena-Blázquez, Silvestra; López-González, Laura; Álvarez-Mon, Miguel Ángel; Pekarek, Tatiana; Casanova, Carlos; Álvarez-Mon, Melchor; Diaz, Raul; Saez, Miguel A.; et al. (Frontiers in Psychology, 2024)
The connection between physical activity and cognitive function has become a focus of attention in educational research in recent years. Regular exercise has been shown to have significant positive effects on physical health, but it also appears to have a significant impact on cognitive function and academic performance. Of all the exercise modalities, resistance training has drawn interest for its ability to improve cerebral abilities in addition to physical well-being. However, there is limited available knowledge exploring the relationship between resistance training regimens and academic performance. This narrative review aims to investigate the underlying mechanisms linking resistance training to academic performance.Firstly, we will examine the biological mechanisms and psychosocial links that potentially connect resistance training to academic performance to find and describe the different mechanisms by which resistance training improves academic performance. In the next part of the work, we delve into the existing observational and intervention studies that have explored the relationship between resistance training and academic performance. Lastly, we provide practical recommendations for including resistance training in institutional education settings, emphasizing the need of dispelling myths and addressing barriers to increase participation as well as the relevance of considering key training variables and adaptation of protocols to developmental stages, always guided by a properly trained professional. Overall, the available evidence supports that resistance training provides potential benefits to the academic performance of youth students with many biological and psychosocial factors that explain this relationship. However, most of the studies are observational, and broader interventional studies are needed to understand and maximize the benefits of this type of physical exercise.